EVALUASI PKRS PADA RSD IDAMAN KOTA BANJARBARU - Liana Fitriani Hasymi; Reny Marliadi; Rizka Ayu Wahyuni; Muhammad Hadarani (LPPM Universitas Awal Bros, 2026)
Hospital Health Promotion (PKRS) is an important part of healthcare services aimed at improving the knowledge, awareness, and healthy behavior of patients and hospital visitors. Evaluation of PKRS implementation is necessary to determine the program's effectiveness and identify aspects that still need improvement. This study aims to disseminate the implementation of PKRS at RSD Idaman, Banjarbaru City based on input, process, output, and impact indicators. The study used a qualitative approach with in-depth interviews with the PKRS Team. The results showed that PKRS implementation has been running quite well, especially in terms of output and impact aspects, including the implementation of activities in various service units and increasing patient understanding of the health services provided. However, several obstacles were still found in the input and process aspects, such as suboptimal training of PKRS officers and the unequal distribution of health promotion media across all areas of the hospital. Therefore, it is necessary to increase human resource capacity, expand health promotion media, and strengthen periodic monitoring and evaluation to improve the effectiveness of PKRS implementation.